Comparative Analysis of Chloroplast Genome Structure and Phylogenetic Relationships Among Six Taxa Within the Genus Catalpa (Bignoniaceae) - Li, Feng; Liu, Ying; Wang, Junhui; Xin, Peiyao; Zhang, Jiangtao; Zhao, Kun; Zhang, Minggang; Yun, Huiling; Ma, Wenjun (Frontiers in Genetics, 2022)
Species or varieties of Catalpa are mostly semievergreen or deciduous trees with opposite or whorled leaves. C. bungei, C. fargesii f. duclouxii and C. fargesii are sources of traditional precious wood in China, known as the "kings of wood". Due to a lack of phenotypic and molecular studies and insufficient sequence information, intraspecific morphological differences, common DNA barcodes and partial sequence fragments cannot clearly reveal the phylogenetic or intraspecific relationships within Catalpa. Therefore, we sequenced the complete chloroplast genomes of 6 species of Catalpa and analyzed their basic structure and evolutionary relationships. The chloroplast genome of Catalpa shows a typical tetrad structure with a total length ranging from 157,765 bp (C. fargesii) to 158,355 bp (C. ovata). The length of the large single-copy (LSC) region ranges from 84,599 bp (C. fargesii) to 85,004 bp (C. ovata), that of the small single-copy (SSC) region ranges from 12,662 bp (C. fargesii) to 12,675 bp (C. ovata), and that of the inverted repeat (IR) regions ranges from 30,252 bp (C. fargesii) to 30,338 bp (C. ovata). The GC content of the 6 chloroplast genomes is 38.1%. In total, 113 unique genes were detected, and there were 19 genes in IR regions. The 113 genes included 79 protein-coding genes, 30 tRNA genes and 4 rRNA genes. Five hypervariable regions (trnH-psbA, rps2-rpoC2, rpl22, ycf15-trnl-CAA and rps15) were identified by analyzing chloroplast nucleotide polymorphisms, which could serve as potential DNA barcodes for the species. Comparative analysis showed that single nucleotide polymorphisms (SNPs) and simple sequence repeats (SSRs) were highly diverse in the six species. Codon usage patterns were highly similar among the Catalpa species or varieties. In addition to the stop codons, all codons showed a preference for ending in A or T. Phylogenetic analysis of the entire chloroplast genome showed that all Catalpa species or varieties formed a monophyletic group, clearly reflecting the relationships within the genus. This study provides information on the chloroplast genome sequence, structural variation, codon bias and phylogeny of Catalpa, which will facilitate future research efforts.